Development of a Monitoring System for Daily Fuel Tank Levels on Ships - Anggara Trisna Nugraha; Moh Ghafirul Pratama Aprilian Sugianto (Journal of Marine Electrical and Electronic Technology, 2024)
Abstract The advancement of technology in maritime engineering has reached remarkable levels, particularly in fuel management systems on ships. However, the majority of fuel tanks still rely on manual monitoring methods, with fuel levels typically displayed using traditional sight glasses. This conventional approach lacks real-time monitoring capabilities and fails to provide data visualization on modern interfaces such as LCD screens, which is a growing demand among operators. Addressing these limitations, this research explores the use of light sensors in conjunction with laser modules to develop an automated monitoring system for daily fuel tanks. Unlike conventional float switches that require direct contact with the fuel, the proposed system utilizes a non-intrusive method. The laser module emits a beam towards the tank, and when the fuel level intersects with the laser, the light sensor detects the reflected ray. This innovative approach enables real-time monitoring of fuel levels, which can be displayed on an LCD screen, enhancing operational efficiency and reducing manual intervention.